1985
DOI: 10.1136/bmj.291.6497.695
|View full text |Cite
|
Sign up to set email alerts
|

AIDS and haemophilia: morbidity and morality in a well defined population.

Abstract: One hundred and forty three multitransfused patients with hereditary haemostatic disorders were examined for evidence of disease related to the acquired immune deficiency syndrome (AIDS). Ninety nine patients with severe haemophilia A were tested for anti-HTLV-III and 76 were found to be positive. All except one of these seropositive patients had received commercial factor VIII concentrates at some time. Eighteen patients with haemophilia B were tested and all were anti-HTLV-III negative. Three out of 36 sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Studies have shown the high incidence of non-A, non-B hepatitis (NANBH) in patients receiving such concentrates for the first time [1,2], and other reports document the transmission of hepatitis B [3] and HIV [4], Heat treatment is an effective means of inactivation of many viruses and can be applied to the lyophilised product. However, experi ence with dry heated factor VIII concentrates suggests that transmission of NANBH is not eliminated by heating for 72 h at 60°C [5] and that, despite the fact that HIV has been shown to be rapidly inactivated at 60 °C in some circum stances [6], patients receiving at least one factor VIII con centrate heated in the lyophilised state for 30 h at 60 °C have seroconverted [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the high incidence of non-A, non-B hepatitis (NANBH) in patients receiving such concentrates for the first time [1,2], and other reports document the transmission of hepatitis B [3] and HIV [4], Heat treatment is an effective means of inactivation of many viruses and can be applied to the lyophilised product. However, experi ence with dry heated factor VIII concentrates suggests that transmission of NANBH is not eliminated by heating for 72 h at 60°C [5] and that, despite the fact that HIV has been shown to be rapidly inactivated at 60 °C in some circum stances [6], patients receiving at least one factor VIII con centrate heated in the lyophilised state for 30 h at 60 °C have seroconverted [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of female partners of men with acquired immunodeficiency syndrome (AIDS) or AIDSrelated conditions (ARC) have found high seropositivity rates, from 36 per cent to 71 per cent,9l1 whereas studies of mostly asymptomatic female partners of seropositive hemophiliacs report much lower rates, from 7 per cent to 15 per cent. [12][13][14] The differences in apparent transmission of HIV in these studies are difficult to explain by sexual practices alone and suggest variation in the infectiousness of the HIV carrier or in the susceptibility to infection of the partner. We report here on an analysis of risk factors for seropositivity to HIV antibody in a group of homosexual men who were regular sexual partners of men who developed AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest infection occurred in 1981; however, most patients were infected during 1983 and 1984 [2], 6-24 months prior to the study. The number of seropositive patients with overt clinical abnormalities (28 %) was only slightly less than the 39% reported from the Newcastle Hemophilia Reference Centre (UK) [3] ; however, the proportion of patients with significant physical incapacity was very low (5%), and only one patient has so far developed AIDS. All patients with clinical signs or symptoms had reduced T-helper cells and T-helper/ suppressor ratios.…”
Section: Discussionmentioning
confidence: 90%
“…Clinical features of HTLV-111 infection have also been described [3] in hemophiliacs, including acquired immune deficiency syndrome (AIDS), lymphadenopathy syndrome, and immune thrombocytopenia; however, the frequency of significant symptomatology has not been well established. The role of this virus in the etiology of immune dysfunction in hemophiliacs also remains controversial.…”
Section: Introductionmentioning
confidence: 96%